Longitudinal study of trachomatous trichiasis in the Gambia. Issue 3 (1st March 2002) - Bowman, R J C; Faal, H; Myatt, M; Adegbola, R; Foster, A; Johnson, G J; Bailey, R L
Abstract : Aim: Investigation of the natural history of trachomatous trichiasis in the Gambia and of the outcome of self epilation and surgery for the condition. Methods: A 1 year longitudinal study of 190 subjects with trichiasis was performed. Major trichiasis cases (five lashes or more) were referred for surgery and minor trichiasis cases were advised to epilate. Outcome measures included progression of trichiasis and corneal scarring; attendance for and results of surgery. Results: 34 of 148 (23%, 95% CI 16 to 31) subjects with major trichiasis attended for surgery over the year. Progression from minor to major trichiasis occurred in 18 of 55 subjects (33%, 95% CI 21 to 47). Progression of corneal scarring occurred in 60 of 167 patients (36%, 95% CI 29 to 44). Clinically active trachoma and conjunctival bacterial isolation predicted progression of corneal opacity. Surgery was successful in 39 of 54 (72%) eyes. Conclusions: Despite the overall decline in trachoma in the Gambia, patients with both minor and major trichiasis remain at risk of developing corneal opacity. Active trachomatous inflammation and additional infection with bacteria may accelerate this process. Antibiotic treatment for trichiasis patients (in addition to surgery) should be investigated. Surgery for minor trichiasis may be indicated. Regular audit of surgical results is necessary with retraining where needed.